EDUKASI PENDEKATAN PARTISIPATIF DALAM PENGENDALIAN HAMA BURUNG DI PERTANAMAN PADI DI KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS KALIMANTAN TENGAH - Tuti, Harlina Kusuma; Sepe, Muslimin; Romadhan, Panji; Rido, Muhammad; Regina, Nurinayah Alfi (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Bird pests in rice cultivation pose a serious problem that directly affects harvest yields and farmer welfare, particularly in Tamban Catur District, Kapuas Regency, Central Kalimantan. This study focuses on implementing an educational program and field practices for bird pest control through a participatory approach. The objective of this research is to enhance farmers' understanding and skills in independently and sustainably managing bird pests. The methods used include training, extension services, and field assistance, involving active participation from farmers. The results show that this program effectively increased farmers' knowledge of bird pest control techniques and significantly reduced harvest losses caused by pest attacks. This participatory approach is expected to be widely applicable in other regions to support food security and improve farmers' welfare.